Age-dependent changes of hindgut microbiota succession and metabolic function of Mongolian cattle in the semi-arid rangelands - Liang, Z.; Zhang, J.; Du, M.; Ahmad, A.A.; Wang, S.; Zheng, J.; Salekdeh, G.H.; Yan, P.; Han Jianlin; Tong, B.; Ding, X. (Frontiers Media, 2022)
Dietary changes have significant effects on gut microbiota and host health. Weaning is an important stage of dietary change in ruminants. The gastrointestinal tract (GIT) microbiota of calf in the early life undergo some changes, and the plasticity of the calf is beneficial to cope with these changes and challenges. However, the complex development of hindgut microorganisms in post-weaning ruminants is not fully understood. In this study, we used 16S rRNA sequencing and untargeted metabolomic analysis to determine the cecal and colonic bacterial community and associated metabolome of Mongolian cattle at age of the 5th (at weaning), 18th, and 36th months. Moreover, the maturation patterns of the hindgut bacterial community and the dynamic changes of metabolites were also explored. Sequencing results showed that Firmicutes and Bacteroidetes were the dominant phyla in the cecum and colon. The linear discriminant analysis (LDA) effect size (LEfSe) analysis revealed bacterial features that were stage-specific in the cecum and colon. The relative abundance of Ruminococcaceae, a microbial family related to fiber degradation, gradually increased with age in the cecum, while the relative abundance of Bacteroides and Alistipes, which are related to immunity, gradually increased in the colon. The differential metabolites in the cecum and colon were mainly enriched in steroid hormone biosynthesis, primary bile acid biosynthesis, and arachidonic acid metabolism between different ages of Mongolian cattle after weaning. Consequently, this dual omics analysis provided important information on the changes in microbial and metabolite interactions in Mongolian cattle after weaning. The microorganisms and metabolites in the cecum and colon further enhanced the abiotic stress resistance of Mongolian cattle to the harsh environment. The information obtained in this study is of great significance for future strategies of cecum and colon microbiota regulation of post-weaning Mongolian cattle in the harsh Mongolian Plateau ecosystem.